Clinical and operative study of otogenic intracranial complications - Siddapur, Geetha Kishan; Sundararajan, B.; Siddapur, Kishan R. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic otitis media is chronic inflammation of the mucoperiostial lining of the middle ear cleft. The prevalence of chronic otitis media and its intracranial complications poses a major public health problem in developing countries like India. By this study; we authors have attempted to highlight the significance of various etiological factors in the occurrence of intracranial complications due to chronic otitis media. Methods: The study was done prospectively in the department of otorhinolaryngology, J.A. group of hospitals, G. R. medical college, Gwalior during the period October 2007-2008. Thirty patients presenting to ear, nose and throat unit, diagnosed as having intracranial complications due to chronic otitis media were included in this study. Results: Most intracranial complications cases were that of meningitis. One third of the cases had past surgical history like mastoid exploration and incision & drainage of post aural abscess, and one fourth of the cases had associated extracranial complications like post aural abscess, lower motor neuron palsy, labrynthitis. Conclusion: The present study and the reference studies, both reveal that the intracranial complications of chronic otitis media are still common till date, and their signs and symptoms are often subtle until late in the course of the disease. Hence, clinicians need to maintain high index of suspicion to avoid delay in diagnosis as morbidity and mortality rates are still high, even with the advent of modern antimicrobials and aggressive surgical intervention.